The Impact of Artificial Intelligence on the Labor Market: https://doi.org/10.55966/assaj.2025.4.1.088 - Huda Qazi (`, 2025)
Artificial Intelligence (AI) is rapidly transforming global labor markets by automating routine tasks, shifting skill requirements, and introducing new occupational roles. The project is first of all a qualitative one, the simple quantitative data on the role of AI in employment should be obtained twofold. On the one hand, it is taking into consideration of the AI in job loss in certain spheres and forming opportunities in other and technology related spheres. Through interviews, industry publications and real-life case studies the paper alludes to how the organizations are transforming and how workers are reacting through reskilling and upskilling. These results are supported by quantitative information on labor trends. The researchers reach the conclusion that judicious investment in education and digital skills and broad policy framework is significant in an attempt to achieve iodic and fair transfer to an AI-absorbed work force. Keywords: Artificial Intelligence, Global Labor Markets, Automating Routine Tasks, Shifting Skill Requirements, New Occupational Roles